Impact of Health Education Program upon Knowledge of Patients with End-Stage Renal Failure - Abbas, ali; Jaddoue, Batool (Iraqi National Journal of Nursing Specialties, 2011)
Objective(s): To determine the impact of health education program toward their end-stage renal failure (ESRF) patients’ knowledge through a follow-up approach each two months post program implementation for six months. Methodology: "Follow-up" longitudinal design by using time series approach of data analysis and the application of pre-post tests approach for the study group and the control group. The study is conducted in Al-Shahid Ghazi Hariri Teaching Hospital for Surgical Specialties/Centre for Disease and Renal Transplant, and Al-Khayal private Hospital for renal disease and transplantation during the period from August, 29th , 2010 through February, 28th , 2011. To achieve the objectives of the study, purposive "non-probability" sample of (40) ESRF patients was taken before operation. The sample is divided equally into study and control groups. Data were collected through the use of questionnaire which is related to ESRF patients’ knowledge test, which were developed for the purpose of the study. Instrument validity was determined through content validity, by a panel of experts. Reliability of the instrument was determined through the use of Pearson correlation coefficient for the test-retest approach, which is (0.82). Analysis of data is performed through the application of descriptive statistics (frequency, percentage) and inferential statistics (t-test and one way analysis of variance). Results: The results of the study indicate that the study group of ESRF patients benefited from the implementation of health education program. However, their knowledge were adequately improved and developed. Recommendation: The study recommends the health education program could be considered as an effective way in the development of knowledge ESRF patients on medical and nursing care after the operation of renal transplantation.